Smokescreen - Johansen, Iris (Johansen, Iris. Eve Duncan forensics thriller., 2019)
In this heart-pounding thriller from #1 New York Times bestselling author Iris Johansen, forensic sculptor Eve Duncan journeys to Africa to help families torn apart by a violent attack deep in the jungle -- but she may be putting herself in more danger than she knows. A journalist shows up on Eve Duncan's doorstep with a plea for help. Jill Cassidy has just come from a small African village with a heart wrenching story: half the villagers -- many of them children -- have been killed in a horrific attack by guerilla soldiers, the bodies burned beyond recognition. Now, the families desperately need Eve's help to get closure and begin to heal. But when Eve arrives in the remote jungle, she begins to suspect that Jill's plea may have been a cover story for a deeper, more sinister plot. Isolated and unsure who she can trust, Eve finds herself stranded in an unstable country where violence threatens to break out again at any moment and with only her own instincts to rely on if she hopes to get home to her family alive... #1 New York Times bestselling author Iris Johansen is back with one of her most exhilarating and dangerous adventures yet in this powerful high-stakes thriller.